The agrarian origins of modern Japan - Smith, Thomas C. (Stanford, Calif. : Stanford University Press, 1959)
The book examines the history of Japanese agriculture which growth can be compared with the growth of agricultural revolution in Europe.
Bibliography: p. [229]-238.
usc 24/01/2019
Loans
Keywords: Land tenure; Agriculture; Japan